2012
DOI: 10.1002/jor.22113
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and characterization of a novel chordoma cell line: CH22

Abstract: Chordoma is a rare primary malignant bone tumor and there exist only a few established human chordoma cell lines. The scarcity of robust chordoma cell lines has limited the ability to study this tumor. In this report, we describe the establishment of a novel chordoma cell line and characterize its in vitro and in vivo behaviors. The tumor tissue was isolated from a patient with recurrent chordoma of the sacrum. After 6 months in culture, the chordoma cell line, referred here as CH22, was established. Microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…Our report of this behavior is both novel and significant, as prior studies of brachyury positivity and copy number aberrations in cultured U-CH2b cells 2 were not predictive of the potential to generate tumor xenografts in vivo, pointing to the need for additional molecular markers to understand tumor progression. Several prior studies have confirmed that morphological appearance, cytoskeletal protein staining (vimentin, cytokeratins), and positivity for S100 and brachyury are essential for characterizing a chordoma xenograft; 11,12,14,20 however, our results suggest that other molecular markers may be needed to distinguish tumorigenic potential and growth kinetics.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Our report of this behavior is both novel and significant, as prior studies of brachyury positivity and copy number aberrations in cultured U-CH2b cells 2 were not predictive of the potential to generate tumor xenografts in vivo, pointing to the need for additional molecular markers to understand tumor progression. Several prior studies have confirmed that morphological appearance, cytoskeletal protein staining (vimentin, cytokeratins), and positivity for S100 and brachyury are essential for characterizing a chordoma xenograft; 11,12,14,20 however, our results suggest that other molecular markers may be needed to distinguish tumorigenic potential and growth kinetics.…”
Section: Discussionsupporting
confidence: 61%
“…11,12,14,20 To date, very few chordoma cell lines have been reported, namely U-CH1 17 and U-CH2b, 2 along with many more putative chordoma cell lines. Only a few of these have been shown to generate tumors in established mouse xenograft models and to retain molecular characteristics of the parent tumor and expanded cells.…”
mentioning
confidence: 99%
“…CH22, another human chordoma cell line, was established in our laboratory as previously reported (23). All cell lines used in this study have been tested and shown to be free of mycoplasma and bacterial.…”
Section: Methodsmentioning
confidence: 99%
“…It can be debated whether these cells are still to be considered true chordoma cells. Chordoma cells tend not to thrive in vitro and proliferate slowly as evidenced by the limited number of commercially available cell lines (19,20). The CH1 and CH2 cells are no different in that respect.…”
Section: Discussion / Conclusionmentioning
confidence: 99%